Efektifitas Mata Kuliah Al Islam Kemuhammadiyahan dalam Pembentukan Akhlakul Karimah Mahasiswa (Studi Deskriptif Analitis di Universitas Muhammadiyah Pekajangan Pekalongan) - Gigih Setianto; Risdiani Risdiani (Universitas Muhammadiyah Jember, 2020)
This article discusses the effectiveness of Al-Islam and Muhammadiyah courses in constructing the morality of students at the University of Muhammadiyah Pekajangan Pekalongan. This article was written using a qualitative descriptive approach with data collection techniques took the form of observation, documentation and interviews. Through the use of these methods, this article found that Al-Islam and Muhammadiyah courses were effective in constructing good morality of the students, both in terms of their ‘noble characters’ (akhlakul karimah) towards Allah, themselves, their family, other people and environment. More specifically, the construction of noble characters towards Allah includes absolute monotheism, praying only to Allah, abstain from believing in superstition, abstain from maintaining amulets, abstain from visiting shamans, being grateful for Allah's blessings, being patient with worldly tests from Allah, worshiping Allah well and properly. The construction of noble characters towards students themselves includes being honest, being a hard worker, trustworthy, disciplined, simple, polite, confident and willing to introspect. The construction of noble characters towards the family includes being devoted to their parents, establishing friendship with the family members maintaining good communication with the family, caring for family members, easing their parents’ burden. The construction of noble characters towards others includes caring for ‘the weak and the helpless’ (mustadzafin), caring to help others, establishing mutual cooperation, and tolerance. At the same time, the construction of noble characters towards the environment includes keeping it clean, using water wisely, reducing plastic waste, rejecting mining which potentially damages the environment, preserving the environment by planting trees and taking care of animals